2015
DOI: 10.1002/ar.23142
|View full text |Cite
|
Sign up to set email alerts
|

Joseon Funerary Texts Tested Using Ancient DNA Analysis of a Korean Mummy

Abstract: In Korea, ancient DNA (aDNA) analysis has been applied to investigations into the genetic affiliations of mummies found in Joseon Dynasty tombs (1392( -1910, becoming now indispensable tool for researches studying human remains from archaeological sites. In the course of our recent examinations on a Korean mummy of Joseon Dynasty, we discovered many teeth contained in a pouch. And in fact, the historical literature on the topic of Joseon funerals contain general accounts of pouches in which an individual's los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…On these bones, it was observed certain microscopic pathological changes such as periosteal deposits, probably syphilitics [11]. These studies complement contemporary investigations of diagenesis of skeleton remains related to the prospects of obtaining a useful DNA profile in cases of skeletonized or partially skeletonized human remains-such as in mass graves [12][13][14], historical [15,16], criminal [17][18][19] or civil forensic cases. Also in the field of forensic investigations burial is a relatively common way of hiding corpses [20].…”
Section: Human Exhumed Bones and Forensicsmentioning
confidence: 79%
“…On these bones, it was observed certain microscopic pathological changes such as periosteal deposits, probably syphilitics [11]. These studies complement contemporary investigations of diagenesis of skeleton remains related to the prospects of obtaining a useful DNA profile in cases of skeletonized or partially skeletonized human remains-such as in mass graves [12][13][14], historical [15,16], criminal [17][18][19] or civil forensic cases. Also in the field of forensic investigations burial is a relatively common way of hiding corpses [20].…”
Section: Human Exhumed Bones and Forensicsmentioning
confidence: 79%
“…Oh et al (2013) showed that aDNA inside mummified brain tissue was less fragmented than that in femurs, thus confirming the brain's status as the preferred sample source for future genetic analysis of Korean mummies. aDNA analysis has also been applied to the autosomal STR of a Joseon mummy, demonstrating that genotyping can be an indispensable tool in archaeological science (Oh et al, 2015a). The above-noted studies have validated the sci-entific potential of Korean mummy specimens as subjects of aDNA analysis.…”
Section: Scientific Value Of Specimens From Joseon Mummiesmentioning
confidence: 86%
“…DNA isolation and purification was performed using a QIAquick PCR purification kit (QIAGEN, Hilden, Germany). The purified DNA was eluted in 50 μl of EB buffer (QIAGEN) [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%